Financial planning & analysis and performance management - Alexander, Jack, 1956- (Wiley, 2018)
"This book is the essential desk reference for CFOs, FP&A professionals, investment banking professionals, and equity research analysts. With thought-provoking discussion and refreshing perspective, this book provides insightful reference for critical areas that directly impact an organization's effectiveness. From budgeting and forecasting, analysis, and performance management, to financial communication, metrics, and benchmarking, these insights delve into the cornerstones of business and value drivers. Dashboards, graphs, and other visual aids illustrate complex concepts and provide reference at a glance, while the author's experience as a CFO, educator, and general manager leads to comprehensive and practical analytical techniques for real world application"- Resumé vydavatel
Terminologický slovník
Keywords: finance podniku; finanční management; investiční bankovnictví; finanční plánování; obchodní podniky; obchodní společnosti; finance; business finance; financial management; investment banking; financial planning; trading companies; corporations; příručky; handbooks and manuals